A reflection on the use of Antidepressants to manage agitation in dementia - M.D.R.D.R.F.D. Basto; L. Santa Marinha; O. Nombora; A. Horta (European Psychiatry, 2022)
Introduction Agitated behaviors is a common neuropsychiatric symptom (NPS) in dementia, defined as inappropriate verbal, vocal, or motor activity that is not thought to be caused by an unmet need. It is frequently reported as a major problem, that impairs the quality of life for the elderly themselves and for caregivers. There has been increasing interest in the use of sedative antidepressants to treat NPS due to concerns over the safety and efficacy of antipsychotics in this setting.